2017
DOI: 10.5539/ijel.v8n2p153
|View full text |Cite
|
Sign up to set email alerts
|

Realizing Learner Autonomy in Pakistan: EFL Teachers’ Beliefs about Their Practices

Abstract: Learner autonomy (LA) has been a key area of interest in foreign language learning and teaching for more than three decades, but a limited space has been awarded to the investigation of teachers' practices in fostering LA. Following an interpretive paradigm and a qualitative approach, present study intended to unearth the strategies teachers of English use to make their learners autonomous. Data were collected through semi-structured interviews with sixteen English teachers from four public universities of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…The negative attitudes of SADA students at UOG might be related to their lack of awareness about the importance of English in their professional lives and their complete focus on practical work. Another reason may be they do not have any external motivation such as lack of instructor's encouragement [18], instructions given in native language and less use of English language in their classrooms.…”
Section: Learner Attitude and Gendermentioning
confidence: 99%
“…The negative attitudes of SADA students at UOG might be related to their lack of awareness about the importance of English in their professional lives and their complete focus on practical work. Another reason may be they do not have any external motivation such as lack of instructor's encouragement [18], instructions given in native language and less use of English language in their classrooms.…”
Section: Learner Attitude and Gendermentioning
confidence: 99%
“…The learning process remains largely learner-centered, in which the learner is autonomous in many respects, for example, not being in a traditional classroom he/she can decide about the suitability of his/her availability to attempt the course tasks. However, interaction with the facilitators creates a bond between the participants and the facilitators as previous research also revealed [22][23][24]. The literature reviewed for this study lacked in focusing on this thematic finding in facilitated MOOC.…”
Section: Sense Of Belongingnessmentioning
confidence: 83%
“…It is also necessary that renewable energy culture should be promoted that can never succeed without creating awareness in youth through their education . This is a feasible situation to start three new dams with reversible turbines on them.…”
Section: Status and Development Of Energy Storage And Transportation mentioning
confidence: 99%